A three-year economic evaluation of a commercial heifer development program - G.C. Lamb; J.M. Lynch; B.L. Miller; V. Traffas; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1998)
In 1994, 1995, and 1996, a commercial heifer development operation purchased a total of 1542 potential replacement heifers. Heifers were purchased in the fall proceeding the spring breeding season and fed a silage-based diet during the developmental period. Before the breeding season began, heifers that failed to meet minimum requirements for pelvic area, average daily gain, body weight, disposition, or structural soundness were culled. During the first year, 42% of 483 heifers were culled, 17% of 468 heifers were culled in the second year, and 14% of 591 heifers in the third year. Estrus was synchronized and heifers were inseminated artificially (AI) for 30 days followed by 30 days of natural mating by cleanup bulls. First-service AI conception rates averaged 68% and overall pregnancy rates (AI + natural mating) averaged 95.1% over the 3-year period. Heifers culled prior to the breeding season realized a net profit of $9 per head, whereas heifers diagnosed nonpregnant after the breeding season lost $86, and heifers that aborted lost $133. Profits for pregnant heifers sold were $163 for first-service AI, $138 for second-service AI, and $83 for bull bred.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Heifer development; Economic evaluation; Replacement Heifers